2020
DOI: 10.2147/opth.s258044
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeting Netrin-1 and -4 as a Novel Diagnostic Parameter and Treatment Option for Diabetic Retinopathy</p>

Abstract: Diabetic retinopathy (DR) is a retinal vascular disorder associated with both type 1 and type 2 diabetes mellitus (DM). It is characterized by specific loss of pericytes, which leads to an augmented blood vessel permeability, and development of new blood vessels (retinal neovascularization). Moreover, stiffening of eye membrane, inflammation, and apoptosis of endothelial cells also lead to damage of the blood-retinal barrier and blindness in most cases unless it's detected and managed early. Hence, this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Targeting VEGF-A, however, is not always beneficial to the patients and is only effective at the late stages of disease when the damage cannot be repaired [ 14 ]. A recent work revisited the knowledge on NTN4 and other netrin receptors in DR and emphasized the number of basic research studies that could have a translational impact in using netrins as DR biomarkers [ 15 ]. However, little is known of its role in DR and/or if netrins can play a role at earlier stages of the pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting VEGF-A, however, is not always beneficial to the patients and is only effective at the late stages of disease when the damage cannot be repaired [ 14 ]. A recent work revisited the knowledge on NTN4 and other netrin receptors in DR and emphasized the number of basic research studies that could have a translational impact in using netrins as DR biomarkers [ 15 ]. However, little is known of its role in DR and/or if netrins can play a role at earlier stages of the pathology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al found that angiogenesis growth factors VEGFC, ANGPT1, ANGPT2, and EFNB2 were upregulated in DR patients, presenting their potentials as biomarkers for DR diagnosis and treatment. 15 Another report demonstrated that netrin-1 and netrin-4 were overexpressed in the DR group, functioning as promising therapeutic agents for DR. 16 Serglycin (SRGN) was a hematopoietic granulosa protein-polysaccharide composed of a relatively small (*17 kDa) core protein. 17 Studies showed that SRGN was mainly expressed in normal hematopoietic cells, endothelial cells, uterine decidua, and embryonic stem cells.…”
Section: Introductionmentioning
confidence: 99%